Smart agroforestry for sustaining soil fertility and community livelihood - Dona Octavia; Murniati; Sri Suharti; Aditya Hani; Nina Mindawati; Suratman; Dila Swestiani; Ahmad Junaedi; Ni Kadek Erosi Undaharta; Purwanto Budi Santosa; Reni Setyo Wahyuningtyas; Varenna Faubiany (Forest Science and Technology, 2023)
AbstractSmart Agroforestry (SAF) is believed to be one of the alternative solutions in implementing sustainable forest management to achieve the community welfare. SAF provides agricultural and silvicultural knowledge and practices that aims not only for recovering the environmental attributes but also for increasing farmers resilience. However, the benefits of agroforestry related to soil fertility in optimizing the land productivity and governing the community livelihood are often overlooked and have not been well discussed. This review aims to describe how smart agroforestry practices in various regions in Indonesia and several other countries have significantly contributed to maintaining soil fertility and increasing crop production while assuring profitable benefits for the community. This review paper focuses on discussing the role of SAF in sustaining soil fertility and community livelihood in tropical and non-tropical regions. The review article was based on a synoptic review approach to SAF and Soil Fertility-related relevant publications and nationwide experiences. The review compiled and analyzed information from national and international research papers in various online scientific journals, conference proceedings and relevant books, to gain a comprehensive understanding of the topic being discussed. The study utilized a qualitative approach and drew upon primary and secondary sources based on a systematic review. Agroforestry has a significant role in recycling soil nutrients from the materials in the surrounding environment. SAF influences soil fertility physically, chemically and biologically. SAF practices in both wet and dry lands can contribute significantly to the community’s income. This review unveils the latent potential and the role of SAF in sustaining soil fertility that supports the community's livelihood and can serve as impetus for future research.